Telaah Pengembangan Kurikulum IPS di Era Merdeka Belajar - Novia Kusumaningsih; Yunita Mahrany (Lembaga Pengembangan Kinerja Dosen, 2024)
After the COVID-19 pandemic, the phenomenon of loss learning forced curriculum changes to become an unavoidable necessity so that the government launched an independent curriculum. The curriculum was developed following the times. The research method used in this research is the library research method or literature study. The author concludes that the independent curriculum is expected to be able to provide concrete and meaningful and effective learning experiences in developing the skills and expertise of students as lifelong learners with Pancasila character. The independent curriculum in social studies learning that focuses on the integration of values and competencies not only encourages intellectual intelligence, but also emotional and social intelligence, such as empathy, social awareness, and effective communication skills. An active and innovative social studies curriculum in independent learning is expected to not only focus on academic achievement, but also on developing students' characters and competencies as socially responsible individuals, while supporting post-pandemic learning recovery.